2023
DOI: 10.1109/jiot.2023.3289625
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Cyber–Physical Systems Security

Abstract: County (UMBC)ScholarWorks@UMBC digital repository on the Maryland Shared Open Access (MD-SOAR) platform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 143 publications
0
2
0
Order By: Relevance
“…Actually, in the text of the analysis of real-world data, besides for change point models, several ways of analyzing financial time series are possible, such as Cherstvy [35], Yu [36], Kantz [37], who introduced three strategies for the analysis of financial time series based on time-averaged observables, which contained the time-averaged mean-squared displacement as well as the aging and delay time methods for the varying fractions of the financial time series. They found that the observed features of the financial time series dynamics agree well with our analytical results for the time-averaged measurables for geometric Brownian motion, underlying the famed Black-Scholes-Merton model.…”
Section: Empirical Applicationsmentioning
confidence: 99%
“…Actually, in the text of the analysis of real-world data, besides for change point models, several ways of analyzing financial time series are possible, such as Cherstvy [35], Yu [36], Kantz [37], who introduced three strategies for the analysis of financial time series based on time-averaged observables, which contained the time-averaged mean-squared displacement as well as the aging and delay time methods for the varying fractions of the financial time series. They found that the observed features of the financial time series dynamics agree well with our analytical results for the time-averaged measurables for geometric Brownian motion, underlying the famed Black-Scholes-Merton model.…”
Section: Empirical Applicationsmentioning
confidence: 99%
“…These outliers usually do not accurately reflect the environmental data and can affect the accuracy of the prediction model to some extent. It may also lead to external attacks on the entire network, affecting the overall operational security [32]. To enhance the precision of prediction algorithms, the availability of dependable initial data is paramount to the efficacy of these algorithms.…”
Section: ) Data Pre-processingmentioning
confidence: 99%
“…The concept of CPS emerged from the integration of embedded computer and communication technologies into various physical domains and sectors. It aims to monitor and control these physical processes effectively [10][11][12]. Many of these systems offer symmetry properties.…”
Section: Introductionmentioning
confidence: 99%